How did Canadian national team athletes manage the COVID-19 pandemic? Athlete, coach, and support staff perspectives to guide future responses to major stressors - Dithurbide, Lori; Boudreault, Véronique; Durand-Bush, Natalie; Delage, Gabriel; MacLeod, Lucy; Gauthier, Véronique (Frontiers in Psychology, 2025)
As we move beyond the pandemic and the lockdowns it imposed on elite athletes, there remains much to learn from how they adapted to this unprecedented crisis. Given the significant impact on their mental health—and the likelihood that they will face other major stressors throughout their careers—this study explored the interplay between the COVID-19 pandemic, mental health, and mental performance among Canadian national team athletes. The perspectives of athletes, coaches, and support staff were examined through focus groups and interviews conducted during the second wave of the pandemic in Canada. Participants included 25 athletes, eight coaches, and five support staff members. Inductive reflexive thematic analysis generated three main themes: (a) consequences of COVID-19 for athletes, (b) factors influencing athlete mental health, and (c) coach and support staff perspectives on well-being and evolving roles. Athletes reported a range of experiences influenced by factors such as isolation, stigma, coping skills, and social support. Mental health and mental performance emerged as core components of a culture of excellence—interrelated and mutually reinforcing. These findings underscore the importance of fostering environments that prioritize well-being alongside performance, particularly as sport organizations prepare for future periods of uncertainty and stress.